(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Pragmatics is the branch of how meaning is influenced by context, such as how sentences in some studying are perceived. The stylistic division focuses on style analysis of literary works in particular but not exclusively in texts. Regarding to Paul Auster’s studies, this paper attempts to address the pragma-stylistic approach, points out the achievement that has been accomplished and needs to be achieved by others. Paul Benjamin Auster is a popular American writer of the contemporary period. His work has received awards the world. So far, from various viewpoints in the West and China, the Critical Group has contributed various critiques to his works.